Problems of Determining the Beginning of the Hijri Calendar at the Al Falah Islamic Boarding School Kediri Perspectives on Falak and Phenomenology: An Astronomical and Phenomenological Analysis - Andhena Wisnu Wardana; Miftahuddin Azmi (Ushuluddin, Adab, and Dakwah Faculty of State Islamic University Ponorogo, 2025)
This study examines the distinctive approach to determining the Hijri calendar (particularly for Ramadan, Shawwal, and Dhu al-Hijjah) practiced by Al-Falah Ploso Kediri Islamic Boarding School, which frequently differs from both government rulings and Nahdlatul Ulama's positions. Employing empirical research methods through structured interviews with key informants, the investigation pursues two primary objectives: first, to analyze the methodological framework employed by Al-Falah in establishing the Hijri calendar; and second, to evaluate this practice through astronomical and phenomenological lenses. The findings reveal that while Al-Falah utilizes multiple calculation methods, its primary reference is the Sullam al-Nayyiroin system, employing a lunar altitude criterion of 2 degrees. Astronomically, this approach falls under the category of hisāb taqrībi (approximate calculation), which demonstrates limited accuracy in light of contemporary astronomical advancements. Phenomenologically, the boarding school's adherence to this traditional method serves to preserve the institutional sanad (chain of transmission) established by its founders, maintaining both scholarly continuity and practical application. This practice holds particular significance for the school's students, alumni, and affiliated communities, while other segments of the population follow government determinations due to limited understanding of the technical considerations. The study highlights the complex interplay between traditional Islamic scholarship, astronomical precision, and community dynamics in contemporary Hijri calendar determination, offering insights into the ongoing discourse surrounding Islamic timekeeping methodologies. REFERENCES Ahmad Izuddin. Fiqih Hisāb Rukyah: Menyatukan Nu Dan Muhammadiyah Dalam Penentuan Awal Ramadhan, Idul Fitri, Dan Idul Adha. Jakarta: Penerbit Erlangga, 2007. Alimuddin. “Hisāb Hakiki: Metode Ilmiah Penentuan Awal Bulan Kamariyah.” Al-Risalah Jurnal Ilmu Syariah Dan Hukum, 2020, 227–35. Antara/ARH. “Beda dengan PBNU, Ponpes Al Falah Kediri Lebaran Besok.” CNN Indonesia, 20 April 2023. https://www.cnnindonesia.com/nasional/20230420203017-20-940372/beda-dengan-pbnu-ponpes-al-falah-kediri-lebaran-besok. Asrohah, Hanun. “THE DYNAMICS OF PESANTREN: Responses toward Modernity and Mechanism in Organizing Transformation.” JOURNAL OF INDONESIAN ISLAM 5, no. 1 (1 Juni 2011): 66–90. https://doi.org/10.15642/JIIS.2011.5.1.66-90. Bogdan. Qualitative Research for Education: An Introduction to Theory and Methods. Boston: Aliyn and Bacon, 1992. Creswell, John W. Research Design: Qualitative and Quantitative. London: Steven & Son, 1994. Dedi Jamaludin. “Penetapan Awal Bulan Kamariah Dan Permasalahannya Di Indonesia.” Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan 4, no. 2 (20 Desember 2018): 156–71. https://doi.org/10.30596/jam.v4i2.2441. Deni, Deni. “Penentuan Awal Ramadhan Syawal dan Dzulhijjah Perspektif Tareqat Naqshabandiyah Al-Khalidiyah Al-Jalaliyah.” Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan 7, no. 1 (2 Juni 2021): 93–102. https://doi.org/10.30596/jam.v7i1.5858. Dhiauddin Tanjung dan Muhammad Hafiz Antassalam. “Penetapan Kalender Hijriah Menurut Ulama Muhammadiyah Dan Nahdatul Ulama Di Indonesia.” Jurnal Edukasi Nonformal 3, no. 2 (2022): 357–66. Dwi Sukmawati. “Analisis Penentuan Awal Bulan Hijriah Dengan Kriteria Baru Mabims Dan Kalender Islam Global.” PhD Thesis, Universitas Gadjah Mada, 2023. https://etd.repository.ugm.ac.id/penelitian/detail/225049. Faridah Hanum. “Mengukuhkan Pesantren Sebagai Basis Pembelajaran Kitab Kuning: Pp. Salafiyah Al Falah Ploso Kediri Jawa Timur.” Al-Qalam 19, no. 1 (9 Januari 2016): 97–106. https://doi.org/10.31969/alq.v19i1.221. Fika Andriana. “Akurasi Hisāb Awal Bulan Qamariah Dalam Kitab Khulashah Al-Wafiyah & Ephemeris.” Jurnal Syariah : Yurisprudensi IAIN Langsa 9, no. 1 (2017): 70–105. H Rohmat. “Penentuan Awal Bulan Qamariyah Menurut Muhammadiyah.” Jurnal Pengembangan Masyarakat, 1, 7 (Februari 2014): 128–45. Hasbiansyah, OJMJK. “Pendekatan fenomenologi: Pengantar praktik penelitian dalam Ilmu Sosial dan Komunikasi.” Mediator: Jurnal Komunikasi 9, no. 1 (2008): 163–80. Hefni, Wildani. “Komodifkasi Agama Dalam Polemik Penentuan Awal Bulan Qamariah Di Indonesia.” Al-Marshad: Jurnal Astronomi Islam Dan Ilmu-Ilmu Berkaitan 6, no. 1 (29 Mei 2020): 75–117. https://doi.org/10.30596/jam.v6i1.4505. Husna, Amirah Himayah. “Unifikasi Kalender Hijriah Nasional Menurut Perspektif Muhammadiyah dan Nahdlatul Ulama.” Al-Afaq: Jurnal Ilmu Falak Dan Astronomi 4, no. 1 (2022): 1–19. Husna, Amirah Himayah, Shirly Ardini, dan Siti Tatmainul Qulub. “Penyatuan Kalender Hijriah Nasional Dalam Perspektif Ormas Muhammadiyah Dan Nahdatul Ulama (NU).” AL - AFAQ : Jurnal Ilmu Falak Dan Astronomi 3, no. 2 (2021): 171–88. https://doi.org/10.20414/afaq.v3i2.4772. Imam Mahdi. “Analisis terhadap kriteria visibilitas hilal Rukyatul Hilal Indonesia (RHI).” Skripsi, Universitas Islam Negeri Walisongo, 2016. http://eprints.walisongo.ac.id/id/eprint/5694/. Irfan Setia Permana Wiantamiharja. “Implementasi Toleransi Beragama Di Pondok Pesantren (studi Kasus Di Pondok Pesantren Universal Bandung).” Hanifiya: Jurnal Studi Agama-Agama 2, no. 1 (2019): 1–15. Jaenal Arifin. “Fiqih Hisāb Rukyah Di Indonesia (Telaah Sistem Penetapan Awal Bulan Qamariyyah).” YUDISIA: Jurnal Pemikiran Hukum dan Hukum Islam 5, no. 2 (2016). Jayusman. Ilmu Falak 2 Fiqh Hisāb Rukyah Penentuan Awal Bulan Kamariah. 1 ed. Banten: MEDIA EDU PUSTAKA, 2021. ———. “Pemikiran Ilmu Falak Kyai Noor Ahmad Ss.” Jurnal Ahkam 2, no. 1 (1 Juli 2014): 20–49. Machzumy. “Kriteria Ideal Lokasi Rukyat.” Syarah: Jurnal Hukum Islam dan Ekonomi 7, no. 2 (2018). Majelis Tarjih dan Tajdid PP. Muhammadiyah. Pedoman Hisāb Muhammadiyah. 2 ed. Yogyakarta, 2009. Masganti Sitorus. Metodologi Penelitian Pendidikan Islam. Medan: IAIN PRESS, 2011. Miftahul Ulum. “Fatwa Ulama Nu (Nahdlatul Ulama) Dan Muhammadiyah Jawa Timur Tentang Hisāb Rukyat.” Jurnal Keislaman 1, no. 2 (1 September 2018): 246. https://doi.org/10.54298/jk.v1i2.3369. Moh Nadhir Muâ. “Analisis Fenomenologi Terhadap Makna dan Realita.” Jurnal Studi Agama Dan Masyarakat 13, no. 1 (2017): 120–35. Mughits. “Kajian Ilmu Falak di Pesantren Salaf di Jawa Tengah dan Jawa Timur.” Asy-Syir’ah: Jurnal Ilmu Syari’ah dan Hukum 50, no. 2 (2016): 379–98. Muhammad Muzayyinul Wathoni. “Penentuan Awal Bulan Kalender Rowot Sasak Perspektif Fikih Dan Astronomi.” AL - AFAQ : Jurnal Ilmu Falak dan Astronomi 3, no. 2 (9 Februari 2022): 109–30. https://doi.org/10.20414/afaq.v3i2.4769. Muhammad Syakir NF. “Atas Petunjuk Kiai, Gus Salam Dan Gus Kautsar Pilih Berkhidmat Di PWNU Jawa Timur.” nu.or.id. Diakses 28 November 2022. https://www.nu.or.id/daerah/atas-petunjuk-kiai-gus-salam-dan-gus-kautsar-pilih-berkhidmat-di-pwnu-jawa-timur-QzWRN. Munawir Pasaribu. “Pembelajaran Ilmu Falak Di Fakultas Agama Islam Universitas Muhammadiyah Sumatera Utara.” Al-Marshad: Jurnal Astronomi Islam Dan Ilmu-Ilmu Berkaitan 6, no. 2 (2020): 207–22. Naufal Firdaus Nurdiansyah. “Berbeda dengan Pemerintah dan PBNU Ponpes Al Falah Ploso, Kediri Tetapkan Ramadhan Sabtu 2 April 2022 -.” Lumajang Network, 2022. https://lumajang.jatimnetwork.com/regional/pr-1803123942/berbeda-dengan-pemerintah-dan-pbnu-ponpes-al-falah-ploso-kediri-tetapkan-ramadhan-sabtu-2-april-2022. Pasaribu, Munawir. “Pembelajaran Ilmu Falak Di Fakultas Agama Islam Universitas Muhammadiyah Sumatera Utara.” Al-Marshad: Jurnal Astronomi Islam Dan Ilmu-Ilmu Berkaitan 6, no. 2 (2020): 207–22. Pribadi, Yanwar. “Religious Networks in Madura: Pesantren, Nahdlatul Ulama, and Kiai as the Core of Santri Culture.” Al-Jami’ah: Journal of Islamic Studies 51, no. 1 (15 Juni 2013): 1–32. https://doi.org/10.14421/ajis.2013.511.1-32. Qomarus Zaman. “Penentuan Awal Bulan Qamariyah Dengan Hisāb Aboge: Studi Kasus Di Desa Ngliman Kecamatan Sawahan Kabupaten Nganjuk.” Empirisma: Jurnal Pemikiran Dan Kebudayaan Islam 31, no. 2 (2022): 149–64. Restu Trisna Wardani dan Ahmad Izzuddin. “A Relevance Between Matla’wilayatul Ḥukmi Towards the Implementation Result of Rukyatul Hilal and Wujudul Hilal.” Al-Hilal: Journal of Islamic Astronomy 2, no. 1 (2020). https://journal.walisongo.ac.id/index.php/al-hilal/article/view/5719. Ridayana. Analisis Penentapan Awal Bulan Kamariah Pondok Pesantren Al Falah Ploso Kediri. Semarang: UIN Walisongo, 2022. Susiknan Azhari. “Saadoe’ddin Djambek Dan Pemikirannya Tentang Hisāb.” Al-Jami’ah: Journal of Islamic Studies 36, no. 61 (1998): 159–80. SusiknanAzhari. Ilmu Falak Teori dan Praktik. Yogyakarta: Lazuardi, 2001. Syaugi Mubarak Seff. “Hisāb-Rukyat Sebagai Metode Penetapan Awal Bulan Qomariyah.” Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman 6, no. 1 (17 Mei 2007). https://doi.org/10.18592/al-banjari.v6i1.967. Taufik. Perkembangan Hisāb Di Indonesia”, Dalam Selayang Pandang Hisāb Rukyah. 1 ed. Jakarta: Direktorat Jenderal Bimas Islam dan Penyelenggaraan Haji Direktorat Pembinaan Peradilan Agama, 2004. Thomas Djamaluddin. “Bismillah, Indonesia Menerapkan Kriteria Baru MABIMS,” 23 Februari 2022. https://tdjamaluddin.wordpress.com/2022/02/23/bismillah-indonesia-menerapkan-kriteria-baru-mabims/.